2018
DOI: 10.1002/lsm.23015
|View full text |Cite
|
Sign up to set email alerts
|

Does blue light restore human epidermal barrier function via activation of Opsin during cutaneous wound healing?

Abstract: Opsins are expressed in the epidermis and dermis of human skin and in the newly regenerating epidermis following wounding. An increase in OPN3 expression in the epithelial tongue may be a potential mechanism for the stimulation of wound closure by blue light. Since keratinocytes and fibroblasts retain their expression of Opsins in culture, they provide a good model to investigate the mechanism of blue light in wound healing responses. Knockdown of OPN3 led to a reduction in early differentiation of keratinocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
94
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(95 citation statements)
references
References 71 publications
(122 reference statements)
1
94
0
Order By: Relevance
“…They found that low levels of blue light did not affect migration or proliferation, but stimulated differentiation of keratinocytes, which was abrogated by OPN3 knockdown. Overall, the current findings on keratinocytes suggest that OPN3 is involved in cell differentiation regulation and restoration of the barrier function 54 …”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…They found that low levels of blue light did not affect migration or proliferation, but stimulated differentiation of keratinocytes, which was abrogated by OPN3 knockdown. Overall, the current findings on keratinocytes suggest that OPN3 is involved in cell differentiation regulation and restoration of the barrier function 54 …”
Section: Resultsmentioning
confidence: 56%
“…In 2018, Pellicena et al reported for the first time that cultured dermal fibroblasts from human facial and abdominal skin tissue express OPN1‐SW, OPN2, and OPN3 54 . Although the function of these opsins in dermal fibroblasts was not elucidated in their study, they inferred from the previous finding showing the anti‐proliferative effect of blue light (450‐490 nm) on fibroblasts in vitro that opsins might be involved in the regulation of cell proliferation 61‐63 .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The choice of the higher fluence (30 J/cm 2 ) stemmed from a study which showed that red light at 656 nm stimulated metabolic activity of primary human epidermal keratinocytes in vitro and increased wound closure ex vivo . 2 The choice of the lower fluence (3.2J/cm 2 ) was guided by previous work where 4 J/cm 2 accelerated migration of oral keratinocytes in vitro 3 and promoted healing of venous ulcers in humans. 4 No differences between the two groups were present with respect to age and Fitzpatrick skin type (I-III).…”
Section: Effects Of Red Light On Inflammation and Skin Barrier Recovementioning
confidence: 99%
“…This is in contrast with previous data which showed a stimulatory effect of red light. 2,8,9 Enhanced skin barrier recovery might have been obtained with repeated irradiations instead of a single irradiation. A delaying effect of blue light on the recovery of the skin barrier was instead observed with a single irradiation with blue light.…”
Section: S K In Surface B I Omarker Smentioning
confidence: 99%